Validating Urinary Neopterin as a Biomarker of Immune Response in Captive and Wild Capuchin Monkeys - Lucore, Jordan M.; Marshall, Andrew J.; Brosnan, Sarah F.; Benítez, Marcela E. (Frontiers in Veterinary Science, 2022)
Non-invasive health monitoring is advantageous for wild and captive primate populations because it reduces the need for traditional invasive techniques (i.e. anesthetization) that can be stressful and potentially harmful for individuals. The biomarker neopterin is an emerging tool in primatology to measure immune activation and immunosenescence, however, most neopterin studies have focused on catarrhine species with little comparative work examining neopterin and health in platyrrhines. To address this gap, we validated a commercially available enzyme-linked immunosorbent assay (ELISA) to measure urinary neopterin in two types of capuchin monkeys, a wild population of white-faced capuchins (Cebus imitator) and a socially housed captive colony of tufted capuchins (Sapajus apella). We analytically validated methods for measuring urinary neopterin in two capuchin populations and demonstrated that two commonly-used methods to control for urine concentration –creatinine and specific gravity (SG)– produced highly concordant results. We also biologically validated these methods by examining variation in neopterin levels based on environment (captive and wild) and age, and changes in levels associated with immune-response. We found that neopterin increased after immune perturbation (rabies vaccine booster), varied by environmental condition, and mirrored expected trends in immune system ontogeny. Our results improve understanding of the innate immune system in platyrrhine species and suggest neopterin may be useful for non-invasive health monitoring in both captive and wild primates.